Housing for three generations with application of universal design - Husin Aljazri, Abdullah; Abdul Rahim, Asiah (2015)
The main objective for this paper is to obtain a framework to allow adaptable and flexible housing solution for multi-generational living by applying universal design approach to make it more user friendly. Malaysian population shall reach 32 million by 2020, and almost 70 percent will be in urban by 2020, today, 63.8 percent is urbanized. Malaysia will also reach ageing nation and the projection of 15 percent of the population will be aged 60 and above in 2050. This calls for a new housing trend that will address these issues. Application of universal design during pre- construction should be encouraged. The methodology applied is by using table research and literature review. Primary data from qualitative approach, including interviews, observation and questionnaire will be analysed. Secondary data from literature, using content analysis will be carried out. This paper will conclude by producing a set of design criteria for three generation housing, which applied universal design approach, which promote financially rewarding to both developers and residents, and to create as a catalyst for the future housing development in Malaysia.